National Outcomes after Pressure Ulcer Closure: Inspiring Surgery. Issue 10 (October 2016) - Diamond, Shawn; Moghaddas, Hassan S.; Kaminski, Stephen S.; Grotts, Jonathan; Ferrigno, Lisa; Schooler, Wesley
Over two million Americans receive treatment for pressure ulcers (PUs) annually, but national surgical outcomes are not well described. This study investigated rates and risk factors of postoperative complications in patients with PU. The 2011 and 2012 American College of Surgeons-National Surgical Quality Improvement Project database was queried and PU patients undergoing flap closure were identified. Descriptive statistics and multivariate regression analysis was used and reported as odds ratios (ORs) if ( P < 0.05). Of 1196 patients identified with a primary diagnosis of PU, 327 (27%) underwent flap closure. Emergency interventions were performed in seven patients who were excluded from analysis. Characteristics were average age 53.3 (±17); 65 per cent male; 41 per cent with grossly contaminated or infected wounds; 29 per cent frail; and 16 per cent with an American Society of Anesthesiologists score of four or five. Myocutaneous or fasciocutaneous flaps were performed in 82 per cent of patients, local skin rearrangements in 17 per cent, and free flap in one patient. Complications were low with 1.9 per cent recurrence and 4.7 per cent reoperation rates. Higher American Society of Anesthesiologists was independently associated with mortality (odds ratio = 6.6) and steroid use correlated with flap failure (odds ratio = 15). No differences in complication profiles were identified based on technique, frailty, or contamination. Surgical closure can be considered reasonable in all patients fit for anesthesia.